Marketing Based on Viral Content SMEs in Indonesia - Hutajulu, Halomoan (Journal of Management, 2024)
This study investigates the relationship between viral content and brand image, as well as the impact on consumer loyalty. This study's data was analyzed using regression analysis. The major conclusion is that viral material has a considerable beneficial impact on brand image. The regression analysis results demonstrate that viral content-based marketing can help a company's brand image. The partial T test findings confirm the significance of viral content in marketing. Although the direct impact on customer loyalty has not been tested, improving branding image through viral content has the potential to affect customer behavior. In conclusion, viral content-based marketing is an excellent method for strengthening branding image and increasing consumer loyalty. Companies that adopt these strategies intelligently can achieve their business goals while also having a good impact on society and the environment.